Fine structural analysis of the fungal polysaccharide pullulan elaborated by aureobasidium pullulans, CH-1 strain - Jakovljević Dragica (Journal of the Serbian Chemical Society, 2001)
The structure of pullulan, the extracellular -D-glucan elaborated by the yeast-like fungus Aureobasidium pullulans, may be described as a linear -D-glucan consisting of maltotriosyl repeat units connected terminally by (1 6)- -D-glucosidic bonds. Occasionally some of maltotriosyl residues are replaced by higher oligosaccharide units, most frequently with maltotetraosyl residues. Using the susceptibility of pullulan CH-1 (obtained from strain CH-1 of Aureobasidium pullulans) to hydrolysis catalysed by porcine alpha-amylase, the polysaccharide was cleaved and the fragments obtained fractionated by gel-permeation chromatography. The heterogenous size of the fragments indicates that there is no apparent regular distribution of tetrasaccharide units in the pullulan chain. Enzymatic digestion of pullulan CH-1 using pullulanase, followed by gel-permeation chromatography of the resulting digest confirmed these results as did preparative paper chromatography and CI mass spectrometry of the separated components, i.e., that maltotetraosyl units (about 7%) are building units of pullulan CH-1.